Early Childhood in Marginalized Roma Communities: Health Risks and Health Outcomes - Filakovska Bobakova, Daniela; Dankulincova Veselska, Zuzana (International journal of public health, 2024)
OBJECTIVES: This study aims to compare selected early childhood health risks and health outcomes of children from marginalized Roma communities (MRCs) in Slovakia with those of the majority. METHODS: We obtained cross-sectional data from mother-child dyads from the majority (N = 109) and MRCs (N = 143) via questionnaires and from medical records. Socioeconomic status, health risks and health outcomes were compared using chi-square and Mann-Whitney U tests in SPSS. RESULTS: Mothers from MRCs reported significantly worse socioeconomic status. Air quality in the households in MRCs was significantly worse, affected by heating with stoves, burning fresh wood and indoor smoking. The diet composition of children from MRCs was characterized by shorter breastfeeding and unhealthy diet composition less fresh fruits and vegetables, more processed meat products, and sweet and salty snacks. Children from MRCs more often suffered from respiratory and diarrheal diseases, used antibiotics and were hospitalized. CONCLUSION: The health and healthy development of children living in MRCs is endangered by various poverty-related factors. Persistent differences in exposures and health in early childhood should be a priority goal of the state's social and health policies.
Keywords: společenská třída; Roma; dieta; Outcome Assessment, Health Care; lidé; hodnocení výsledků zdravotní péče; Cross-Sectional Studies; Diet; předškolní dítě; Social Class; Romové; Child, Preschool; průřezové studie; Humans